Chicken feed, or, Wages for wives : a comedy in three acts / by Guy Bolton ; staged by Winchell Smith. - Bolton, Guy, 1884-1979. (Tufts University. Tisch Library., 2019)
New York : Samuel French, [1924]; 1 online resource (105 pages, 4 unnumbered leaves of plates) : illustrations.